ENQUIRE OF THE IMPLEMENTATION OF EDUCATIONAL FUNCTION ON TELEVISI REPUBLIK INDONESIA (TVRI) AS A PUBLIC BROADCASTING INSTITUTION - Ade Armando; Pinckey Triputra; Ezki Tri Rezeki Widianti (Profetik: Jurnal Komunikasi, 2023)
The function of education is traditionally attached to the role of the Public Broadcasting Service (PBS). Televisi Republik Indonesia (TVRI), stated in the Broadcasting Act 32/2002 as one of the public broadcasting institutions, along with Radio Republik Indonesia (RRI), are to carry out this educational function. This article will analyze the education function performed by TVRI. This research employs a single case study design. Data obtained through interviews and literature review. The results of the study show that educational broadcasts on TVRI have been around for a long time. The results of the documentation study show that educational broadcasts on TVRI receive a positive response from the public. Field research shows that one of the educational programs on TVRI, Study from Home (henceforth referred to as Belajar Dari Rumah/ BDR) has outperformed other public programs. Although traditionally considered one of the main functions of public television, the implementation of educational broadcasts, especially formal education on TVRI is not consistently carried out. The absence of formal education programs at TVRI was due to technical constraints in the form of a lack of compatible studio equipment to record formal education programs and unavailable budgets for the programs..